Indigenous Australian Life Histories - A New Genre of Writing and Publishing? - Seal, Graham (Australia by Common Ground Publishing Pty Ltd, 2006)
This paper looks at the development of a new 'writing' and publishing genre of Aboriginal life history that seems to have originated with Magabala Books, Broome, WA, since the 1990s. A number of relevant titles are discussed, the genre is described and observations about the cultural and social significance of the genre are made, together with some probing of the publishing processes involved. The paper is divided into four sections: Description of the genre and its characteristics; Processes of generating a primary 'manuscript' – technological and human; The publishing process; Concluding analysis of the overall significance of what has been observed and raising pertinent issues for discussion.